A low temperature cured acrylic powder coating and a method of making the same

CN122978786APending Publication Date: 2026-10-27WUXI CHANGCHUAN MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611209761.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]然而,现有技术中这类丙烯酸粉末涂料的固化温度普遍偏高,常规热风循环固化工艺通常需要达到175℃至200℃

Benefits of technology

1、本申请低温固化丙烯酸粉末涂料,在显著降低固化温度的条件下,仍能使涂膜形成高度致密的交联网络,从而兼具优异的物理防护与化学防护性能;且该涂料尤其适用于对温度敏感的基材,在有效降低涂装能耗的同时,还能确保涂层具有卓越的耐湿热防水、耐水渗透及耐腐蚀能力,且涂层自身具备良好的力学性和使用稳定性,能够满足多个性能要求较高的应用领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the field of powder coatings, in particular to a low-temperature curing acrylic powder coating and a preparation method thereof. The raw material scheme of the low-temperature curing acrylic powder coating comprises an acrylic resin, a filler, a curing agent, an accelerator, an antioxidant, an ultraviolet absorber and a reinforcing agent and the like. The low-temperature curing acrylic powder coating of the application can still enable a coating film to form a highly compact crosslinking network under the condition of significantly reducing the curing temperature, thereby having excellent physical protection and chemical protection performances; and the coating is particularly suitable for temperature-sensitive substrates, can effectively reduce coating energy consumption, can ensure that the coating has excellent moisture-proof, water permeation resistance and corrosion resistance, and the coating itself has good mechanical properties and use stability, and can meet the requirements of multiple application fields with high performance requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of powder coatings, and in particular to a low-temperature curing acrylic powder coating and its preparation method. Background Technology

[0002] Powder coatings, due to their absence of organic solvents and near-zero VOC emissions, have become an important development direction in the field of environmentally friendly coatings, and are increasingly widely used in industries such as automobiles, home appliances, and building decoration. Among the many types of powder coatings, acrylic powder coatings, with their excellent decorative properties, superior weather resistance, good stain resistance, and high surface hardness and wear resistance, are widely used in high-performance applications such as automotive aluminum wheels and high-end home appliance topcoats.

[0003] Currently, acrylic powder coatings typically employ thermosetting resin systems. These systems utilize specific reactive functional groups within the resin to undergo a cross-linking reaction with a compatible curing agent under heating conditions, forming a dense coating film with a three-dimensional network structure. This curing system imparts excellent comprehensive physical and chemical properties to the coating, including good adhesion, flexibility, impact resistance, and chemical resistance, thus becoming one of the main solutions for high-performance powder coating.

[0004] However, the curing temperature of existing acrylic powder coatings is generally too high, typically requiring 175°C to 200°C for conventional hot air circulation curing processes. This high curing temperature not only increases production costs but also severely limits the application of powder coatings on heat-sensitive substrates such as plastics and wood. Furthermore, in applications such as automotive aluminum wheel coating, high-temperature curing can lead to thermal deformation or a decline in the mechanical properties of the substrate. Moreover, mature solutions for low-temperature curing systems required for multi-layer coating processes are still lacking.

[0005] To further address the aforementioned application issues, in recent years, researchers in this field have attempted to lower the curing temperature of acrylic powder coatings to below 160°C or even lower. However, the new technical problem brought about by low-temperature curing is that the crosslinking reaction is difficult to complete, resulting in insufficient crosslinking density of the coating, which leads to a decrease in the density of the coating film and a decline in comprehensive performance such as corrosion resistance and weather resistance. At the same time, mechanical properties such as flexibility and impact resistance are also difficult to maintain.

[0006] Therefore, how to ensure that acrylic powder coatings have sufficiently high crosslinking density, excellent weather resistance and corrosion resistance, as well as good appearance and comprehensive mechanical properties while significantly reducing the curing temperature has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0007] To address the aforementioned issues, the applicant has provided the following technical solutions: A low-temperature curing acrylic powder coating, by weight, comprises the following raw materials: 75-90 parts acrylic resin, 8-15 parts filler, 3-6 parts curing agent, 0.5-1.5 parts accelerator, 1-2 parts leveling agent, 0.5-1 part degassing agent, 0.2-0.3 parts antioxidant, 0.3-0.4 parts ultraviolet absorber, 1.2-2.5 parts reinforcing agent, and 2-5 parts pigment.

[0008] In a preferred embodiment, the acrylic resin is a combination of GMA acrylic resin and auxiliary acrylic resin.

[0009] In a preferred embodiment, the mass ratio of the GMA acrylic resin to the auxiliary acrylic resin is (7~8.5):(0.8~1.3).

[0010] In a preferred embodiment, the mass ratio of the GMA acrylic resin to the auxiliary acrylic resin is (7.5~8):(0.9~1.2).

[0011] In a preferred embodiment, the epoxy equivalent of the GMA acrylic resin is 450~600 g / eq.

[0012] In a preferred embodiment, the auxiliary acrylic resin is a low-epoxy GMA acrylic resin.

[0013] In a preferred embodiment, the epoxy equivalent of the low-epoxy GMA acrylic resin is 250~330 g / eq.

[0014] In a preferred embodiment, the mass ratio of the acrylic resin to the reinforcing agent is (8~9):(0.14~0.23).

[0015] In a preferred embodiment, the mass ratio of the acrylic resin to the reinforcing agent is (8.2~8.6):(0.16~0.2).

[0016] By compounding a high-epoxy-equivalent rigid alicyclic GMA acrylic resin with a low-epoxy-equivalent highly reactive GMA acrylic resin, the core contradiction of insufficient crosslinking density under low-temperature curing conditions is resolved while ensuring excellent overall application performance. The introduction of the rigid alicyclic structure lowers the activation energy of molecular chain movement at low temperatures, allowing epoxy groups to acquire sufficient mobility to approach the curing agent and react at lower temperatures. Meanwhile, the low-epoxy-equivalent resin provides more reactive sites, compensating for the reduced crosslinking points caused by the slower reaction rate at low temperatures. Crosslinking and crosslinking enhancement occur simultaneously, enhancing the extrusion of the coating's mechanical properties and providing the greatest foundation for improving excellent overall performance.

[0017] In a preferred embodiment, the filler is at least one of precipitated barium sulfate, heavy calcium carbonate, talc, mica powder, and kaolin.

[0018] In a preferred embodiment, the filler is precipitated barium sulfate or mica powder.

[0019] In a preferred embodiment, the filler is precipitated barium sulfate.

[0020] In a preferred embodiment, the average particle size of the filler is 2.5~6μm.

[0021] In a preferred embodiment, the average particle size of the filler is 2.5~4μm.

[0022] In a preferred embodiment, the curing agent is dodecyl dicarboxylic acid.

[0023] In a preferred embodiment, the promoter is 2-methylimidazole, 2-ethyl-4-methylimidazole, or ethyltriphenylphosphonium bromide.

[0024] In a preferred embodiment, the promoter is 2-methylimidazole or 2-ethyl-4-methylimidazole.

[0025] In a preferred embodiment, the promoter is 2-methylimidazole.

[0026] In a preferred embodiment, the leveling agent is a polybutyl acrylate leveling agent or a polysiloxane leveling agent.

[0027] In a preferred embodiment, the leveling agent is a polysiloxane leveling agent.

[0028] In a preferred embodiment, the degassing agent is benzoin or microcrystalline wax.

[0029] In a preferred embodiment, the degassing agent is benzoin.

[0030] In a preferred embodiment, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant B225.

[0031] In a preferred embodiment, the antioxidant is antioxidant 1076 and / or antioxidant 168.

[0032] In a preferred embodiment, the antioxidant is a combination of antioxidant 1076 and antioxidant 168.

[0033] In a preferred embodiment, the mass ratio of antioxidant 1076 to antioxidant 168 is (1~1.5):(1~1.5).

[0034] In a preferred embodiment, the mass ratio of antioxidant 1076 to antioxidant 168 is 1:1.2.

[0035] In a preferred embodiment, the ultraviolet absorber is at least one of Tinuvin 320, Tinuvin 928, UV-531, and Tinuvin 328.

[0036] In a preferred embodiment, the ultraviolet absorber is Tinuvin 320 or UV-531.

[0037] In a preferred embodiment, the reinforcing agent is a combination of phytic acid, zinc acetylacetonate, and sodium benzotriazole.

[0038] In a preferred embodiment, the mass ratio of phytic acid, zinc acetylacetonate, and sodium benzotriazole is (3~5):(2~3.5):(4~6).

[0039] In a preferred embodiment, the mass ratio of phytic acid, zinc acetylacetonate, and sodium benzotriazole is (4~4.5):(2.4~3):(4~5).

[0040] This application further incorporates a reinforcing agent, which continuously participates in the cross-linking reaction during the curing process, thereby continuously enhancing the density of the coating throughout the curing process. This provides a reliable carrier environment for the stable immobilization of subsequent protective components. Furthermore, a chemically bonded passivation layer is formed on the substrate surface, and further protected by sodium benzotriazole, strengthening the protective barrier and ensuring the tightness of the system. During use, the internal system and the film layer will not fail due to moisture migration. It also compensates for any weak adhesion points that may exist at the microscopic interface of the coating body, promoting the coating system to improve its comprehensive performance in terms of resistance to damp heat, water resistance, and corrosion resistance under low-temperature curing conditions.

[0041] In a preferred embodiment, the pigment is titanium dioxide, titanium dioxide, or zinc barium white.

[0042] In a preferred embodiment, the pigment is titanium dioxide or titanium dioxide.

[0043] A method for preparing the above-mentioned low-temperature curing acrylic powder coating specifically includes the following steps: S1: Crush and sieve the acrylic resin using a grinding mill, accurately weigh each raw material according to the formula, and mix them all in a high-speed mixer to obtain a mixture; S2: Feed the mixture into a twin-screw extruder, with an extruder temperature range of 90~130℃ and a screw speed of 40~45rpm, and press the extrudate into sheets using cooling rollers; S3: Crush the sheets using a sheeting crusher and feed them into a grinding mill to grind them into powder, sieve the powder, and cure it completely at 140~150℃ for 20~40 minutes before use to obtain the final product.

[0044] The preferred embodiment of the preparation method of the low-temperature curing acrylic powder coating specifically includes the following steps: S1: The acrylic resin is pulverized through a mill to a mesh size of 150-200. The raw materials are accurately weighed according to the formula and put into a high-speed mixer at a speed of 600-800 rpm for 15-20 minutes to obtain a mixture; S2: The mixture is fed into a twin-screw extruder at a temperature of 90-100℃ in zone 1, 120-130℃ in zone 2, 100-105℃ in zone 3, and 90-95℃ at the die head, with a screw speed of 40-45 rpm. The extrudate is pressed into sheets by cooling rollers; S3: The sheets are crushed to ≤5mm by a sheeting crusher and then ground into powder by a mill. The powder is sieved through a 200-300 mesh sieve and cured completely at 140-150℃ for 20-40 minutes before use to obtain the final product.

[0045] Beneficial effects of the application plan: 1. The low-temperature curing acrylic powder coating of this application can still form a highly dense cross-linked network in the coating film under the condition of significantly reducing the curing temperature, thus possessing both excellent physical and chemical protection properties; and this coating is particularly suitable for temperature-sensitive substrates, effectively reducing coating energy consumption while ensuring that the coating has excellent resistance to damp heat and water, water penetration and corrosion, and the coating itself has good mechanical properties and service stability, which can meet the needs of many application fields with high performance requirements.

[0046] 2. This application solves the core problem of insufficient crosslinking density under low-temperature curing conditions by compounding a rigid alicyclic GMA acrylic resin with a high epoxy equivalent with a high reactive GMA acrylic resin with a low epoxy equivalent, while ensuring good comprehensive application performance.

[0047] 3. This application further incorporates a reinforcing agent, which continuously participates in the cross-linking reaction during the curing process, thereby continuously enhancing the density of the coating throughout the curing process. This provides a reliable carrier environment for the stable immobilization of subsequent protective components. Furthermore, a chemically bonded passivation layer is formed on the substrate surface, and further protected by sodium benzotriazole, strengthening the protective barrier and ensuring the tightness of the system. During use, the system interior and the film layer will not fail due to moisture migration. It also compensates for any weak adhesion points that may exist at the microscopic interface of the coating body, promoting the coating system to improve its comprehensive performance in terms of resistance to damp heat, water resistance, and corrosion resistance under low-temperature curing conditions. Detailed Implementation

[0048] Example 1 A low-temperature curing acrylic powder coating, by weight, comprises the following raw materials: 85 parts acrylic resin, 10.5 parts filler, 3.8 parts curing agent, 0.8 parts accelerator, 1.2 parts leveling agent, 0.6 parts degassing agent, 0.3 parts antioxidant, 0.3 parts ultraviolet absorber, 2 parts reinforcing agent, and 4 parts pigment.

[0049] The acrylic resin is a combination of GMA acrylic resin and low-epoxy GMA acrylic resin in a mass ratio of 7.6:0.9.

[0050] The GMA acrylic resin is specifically Almatex PD7610, with an epoxy equivalent of 540 g / eq, from Mitsui Chemicals, Japan; the low-epoxy GMA acrylic resin is specifically SA300, with an epoxy equivalent of 300 g / eq, from Liuan Jietongda New Materials, China.

[0051] The filler is precipitated barium sulfate with an average particle size of 3 μm; the curing agent is dodecyl dicarboxylic acid; the accelerator is 2-methylimidazole; the leveling agent is polysiloxane leveling agent BYK-333; the degassing agent is benzoin; the ultraviolet absorber is Tinuvin 320; and the pigment is titanium dioxide with an average particle size of 0.5 μm.

[0052] The antioxidant is a combination of antioxidant 1076 and antioxidant 168 in a mass ratio of 1:1.2.

[0053] The reinforcing agent is a combination of phytic acid, zinc acetylacetonate, and sodium benzotriazole in a mass ratio of 4.2:2.8:4.5.

[0054] A method for preparing the above-mentioned low-temperature curing acrylic powder coating specifically includes the following steps: S1: The acrylic resin is pulverized through a 200-mesh mill, and each raw material is accurately weighed according to the formula and put into a high-speed mixer at 800 rpm for 20 minutes to obtain a mixture; S2: The mixture is fed into a twin-screw extruder at 100°C in zone 1, 125°C in zone 2, 105°C in zone 3, and 95°C at the die head, with a screw speed of 45 rpm. The extrudate is pressed into sheets by cooling rollers; S3: The sheets are crushed to ≤5mm by a sheet crusher and then ground into powder by a mill. The powder is sieved through a 200-300 mesh sieve and cured completely at 150°C for 30 minutes before use to obtain the final product.

[0055] Example 2 A low-temperature curing acrylic powder coating, different from Example 1: The low-temperature curing acrylic powder coating, by weight, comprises the following raw material scheme: 90 parts acrylic resin, 11.5 parts filler, 4 parts curing agent, 0.9 parts accelerator, 1.2 parts leveling agent, 0.6 parts degassing agent, 0.3 parts antioxidant, 0.3 parts ultraviolet absorber, 1.5 parts reinforcing agent, and 4 parts pigment.

[0056] Example 3 A low-temperature curing acrylic powder coating, different from Example 1: The low-temperature curing acrylic powder coating, by weight, comprises the following raw material scheme: 80 parts acrylic resin, 10 parts filler, 3.6 parts curing agent, 0.8 parts accelerator, 1.2 parts leveling agent, 0.6 parts degassing agent, 0.3 parts antioxidant, 0.3 parts ultraviolet absorber, 1.8 parts reinforcing agent, and 4 parts pigment.

[0057] Comparative Example 1 A low-temperature curing acrylic powder coating, different from Example 1: The low-temperature curing acrylic powder coating, by weight, comprises the following raw material scheme: 105 parts acrylic resin, 13.5 parts filler, 4.5 parts curing agent, 1.2 parts accelerator, 1.5 parts leveling agent, 0.8 parts degassing agent, 0.3 parts antioxidant, 0.4 parts ultraviolet absorber, 0.8 parts reinforcing agent, and 4.2 parts pigment.

[0058] Comparative Example 2 A low-temperature curing acrylic powder coating, different from Example 1: The low-temperature curing acrylic powder coating, by weight, comprises the following raw material scheme: 80 parts acrylic resin, 9.5 parts filler, 3.8 parts curing agent, 0.8 parts accelerator, 1.2 parts leveling agent, 0.6 parts degassing agent, 0.3 parts antioxidant, 0.3 parts ultraviolet absorber, 4.8 parts reinforcing agent, and 4 parts pigment.

[0059] Comparative Example 3 A low-temperature curing acrylic powder coating, differing from Example 1, uses a combination of GMA acrylic resin and low-epoxy GMA acrylic resin in a mass ratio of 8.2:0.3. Comparative Example 4 A low-temperature curing acrylic powder coating, which differs from Example 1, uses an acrylic resin that is a combination of GMA acrylic resin and low-epoxy GMA acrylic resin in a mass ratio of 6.5:2.

[0060] Comparative Example 5 A low-temperature curing acrylic powder coating, different from Example 1, wherein the reinforcing agent is a combination of phytic acid, zinc acetylacetonate and sodium benzotriazole in a mass ratio of 6:4:1.5.

[0061] Comparative Example 6 A low-temperature curing acrylic powder coating, different from Example 1, wherein the reinforcing agent is a combination of phytic acid, zinc acetylacetonate and sodium benzotriazole in a mass ratio of 2:4.5:5.

[0062] Performance Evaluation 1. Hardness: Tested according to ASTM D-3363-92, and the results are recorded in Table 1.

[0063] 2. Thermal cycling shock: The test references GM9525P, with 8 cycles from -30℃×1h to 70℃×1h. After the 8 cycles, use a soft brush to gently sweep away debris along the diagonal of the grid. Apply a 25mm wide transparent tape with an adhesion strength greater than 2.94N / 10mm to the grid and press it firmly. Let it stand for 2 minutes, then peel the tape off smoothly at a 60° angle within 1 second. Observe whether there is any peeling, cracking, or blistering on the coating surface. If any phenomenon is present, it is considered unqualified; otherwise, it is considered qualified. 50 groups were tested for each example, and the pass rate was recorded in Table 1.

[0064] 3. Impact resistance to crushed stone: The test is conducted according to ASTM D-3170-80. The coated sample is installed in the crushing resistance test device. 500g of standard crushed stone with a particle size range of 9.5~16mm is sprayed onto the test plate with compressed air at a pressure of 100kPa. The spraying distance is 300mm and the spraying angle is 45°. After the impact, the test plate is cleaned and observed for any peeling or cracking of the coating. If any phenomenon is found, it is considered unqualified; otherwise, it is considered qualified. 50 sets are tested for each example, and the pass rate is recorded in Table 1.

[0065] 4. Salt spray corrosion resistance: Using a blade, make a cross-shaped X-shaped scratch penetrating the coating to the substrate on the coated sample. Each scratch is 50 mm long and 1 mm wide. Place the sample in a salt spray test chamber at a temperature of 35±1℃, with a salt spray solution of 5±0.5% NaCl and a pH value between 6.8 and 7.2. The spray volume is 2 ml / 80 cm²·h. The sample is placed at a 30° angle to the vertical direction with the scratch facing upwards. After spraying continuously for 1000 h, remove the sample, rinse the surface with clean water to remove residual salt, and blow dry. Observe the corrosion spread of the coating at the scratch and measure the maximum corrosion width on both sides of the scratch. The results are recorded as the average of 5 test groups in Table 1.

[0066] 5. CASS salt spray resistance: Test reference GM4476P, evaluate the results according to the standard after 240h test and record them in Table 2.

[0067] 6. Resistance to damp heat: The test is conducted according to ASTM D-2247-99. After 1000 hours of testing, check whether the coating shows signs of blistering, peeling, or loss of gloss. If any of these phenomena are observed, the coating is considered unqualified; otherwise, it is considered qualified. 50 sets of samples are tested for each example, and the pass rate is recorded in Table 2.

[0068] 7. Water resistance: The test references GM4666P, with a standard immersion time of 240h. After the test, observe whether there is blistering or peeling of the coating. If either phenomenon is present, it is considered unqualified; otherwise, it is considered qualified. 50 groups are tested for each example, and the pass rate is recorded in Table 2.

[0069] 8. Weather resistance: The test is conducted according to ASTM G-155, with a test time of 1000h. After the test, the 60° gloss is measured and the gloss retention rate is calculated. The result is the average of 10 tests and recorded in Table 1.

[0070] Table 1 Performance Evaluation 1 Table 2 Performance Evaluation 2 As can be seen from the performance evaluation table, Examples 1-3 achieved superior performance test results compared to Comparative Examples 1-6. The corresponding technical solutions specified in this application adopted in Examples 1-3 solved the core contradiction of insufficient crosslinking density under low temperature curing conditions, while ensuring good comprehensive performance. Furthermore, the addition of a suitable ratio of reinforcing agent provided a reliable carrier environment for the stable fixation of subsequent protective components, compensated for the possible adhesion weaknesses of the coating body at the micro-interface, and promoted the coating system to improve its comprehensive performance such as resistance to damp heat, water resistance, and corrosion resistance under low temperature curing conditions.

[0071] Comparative Examples 1 to 6 adopted corresponding technical solutions different from those specified in this application. Consequently, the changes in technical solutions directly led to a decrease in the technical effect of the corresponding raw materials in the system, a decrease in the performance balance effect, and an inability to fully compensate for the weak points of adhesion. Ultimately, the overall comprehensive performance was significantly lower than that of Examples 1 to 3.

Claims

1. A low-temperature curing acrylic powder coating, characterized in that: The raw material formula includes: 75-90 parts acrylic resin, 8-15 parts filler, 3-6 parts curing agent, 0.5-1.5 parts accelerator, 1-2 parts leveling agent, 0.5-1 part degassing agent, 0.2-0.3 parts antioxidant, 0.3-0.4 parts ultraviolet absorber, 1.2-2.5 parts reinforcing agent, and 2-5 parts pigment; The acrylic resin is a combination of GMA acrylic resin and auxiliary acrylic resin, with a mass ratio of (7~8.5):(0.8~1.3). The epoxy equivalent of the GMA acrylic resin is 450~600 g / eq; The reinforcing agent is a combination of phytic acid, zinc acetylacetonate and sodium benzotriazole, in a mass ratio of (3~5):(2~3.5):(4~6).

2. The low-temperature curing acrylic powder coating according to claim 1, characterized in that: The mass ratio of the acrylic resin to the reinforcing agent is (8~9):(0.14~0.23).

3. The low-temperature curing acrylic powder coating according to claim 2, characterized in that: The filler is at least one of precipitated barium sulfate, heavy calcium carbonate, talc, mica powder, and kaolin.

4. The low-temperature curing acrylic powder coating according to claim 3, characterized in that: The average particle size of the filler is 2.5~6μm.

5. The low-temperature curing acrylic powder coating according to claim 4, characterized in that: The curing agent is dodecyl dicarboxylic acid.

6. The low-temperature curing acrylic powder coating according to claim 5, characterized in that: The accelerator is 2-methylimidazole, 2-ethyl-4-methylimidazole, or ethyltriphenylphosphonium bromide.

7. The low-temperature curing acrylic powder coating according to claim 6, characterized in that: The degassing agent is benzoin or microcrystalline wax.

8. The low-temperature curing acrylic powder coating according to claim 7, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 168 and antioxidant B225.

9. The low-temperature curing acrylic powder coating according to claim 8, characterized in that: The ultraviolet absorber is at least one of Tinuvin 320, Tinuvin 928, UV-531 and Tinuvin 328.

10. A method for preparing a low-temperature curing acrylic powder coating according to any one of claims 1 to 9, characterized in that: Specifically, the following steps are included: S1: Crush and sieve the acrylic resin using a pulverizer. Accurately weigh each raw material according to the formula and put them all into a high-speed mixer to mix and obtain a mixture. S2: Feed the mixture into a twin-screw extruder. The extruder temperature range is 90~130℃ and the screw speed is 40~45rpm. The extrudate is pressed into sheets by cooling rollers. S3: The sheets are crushed by a sheet crusher and then fed into a pulverizer to be ground into powder. The powder is sieved and then cured completely at 140~150℃ for 20~40 minutes before use.